Convergence rates for the strong law of large numbers under association - Henriques, Carla (2008)
We prove convergence rates for the Strong Laws of Large Numbers (SLLN) for associated variables which are arbitrarily close to the optimal rates for independent variables. A rst approach is based on exponential inequalities, a usual tool for this kind of problems. Following the optimization e orts of several authors, we improve the rates derived from exponential inequalities to log2 n n1=2 . A more recent approach tries to use maximal inequalities together with moment inequalities. We prove a new maximal order inequality of order 4 for associated variables, using a telescoping argument. This inequality is then used to prove a SLLN convergence rate arbitrarily close to log1=4 n n1=2 .